Ion-neutral coupling in the high-latitude F-layer from incoherent scatter and Fabry-Perot interferometer measurements - Cierpka, K.; Kosch, M. J.; Rietveld, M.; Schlegel, K.; Hagfors, T. (CCSD, 2000)
International audience Since the auroral ionosphere provides an important energy sink for the magnetosphere, ionosphere-thermosphere coupling must be investigated when considering the energy budget of the ionosphere-magnetosphere coupling. We present the first Scandinavian ground-based study of high-latitude F-region ion-neutral frictional heating where ion velocity and temperature are measured by the EISCAT incoherent scatter radar as well as neutral wind and temperature being measured simultaneously by a Fabry-Perot interferometer. A geomagnetically active period ( K p = 7 ? ? 5 ? ) and quiet period ( K p = 0 + ? 0) were studied. Neglecting the neutral wind can result in errors of frictional heating estimates of 60% or more in the F-layer. About 96% of the local ion temperature enhancement over the neutral temperature is accounted for by ion-neutral frictional heating. Key words: Ionosphere (auroral ionosphere; ionosphere-atmosphere interactions)